PERUBAHAN STRUKTUR EKONOMI KABUPATEN MANGGARAI BARAT TAHUN 2000-2020 - Dangu, Ursula (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044], 2022)
The purpose of this study was determine changes in economic structure of the West Manggarai Regency and the leading sectors in West Manggarai Regency. This research was conducted in West Manggarai Regency, East Nusa Tenggara. The analytical technique used in this research is descriptive analysis and shift share. Descriptively it was found that the economic growth of West Manggarai Regency experienced a relatively slow movement. This shift was caused by changes in the contribution of the economic sector where the contribution of the agricultural sector slowly decreased so that it shifted from the agricultural sector to the service sector and the leading sector in West Manggarai district was the service sector. The industrial sector is experiencing relatively fast growth. Keywords:changes instructure, GDP, labor  and shift share